FAKTOR YANG MEMENGARUHI KINERJA KEUANGAN PERBANKAN DENGAN RISIKO KREDIT SEBAGAI MODERASI - Jason Lee; Herlin Tundjung Setijaningsih (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to identify the effect of capital, liquidity, and operational efficiency on the financial performance of banking with credit risk as a moderating variable in banking companies listed in the Indonesia Stock Exchange (IDX) during the year 2016-2020. The data obtained are 125 data from 25 total banking samples. Furthermore, data collection techniques used in this research is purposive sampling that is processed using Eviews version 12 program. The result of this study concludes that capital and liquidity has no sinificant effect on financial performance of banking, while operational efficiency has a negative effect on financial performance of banking. The result concludes that credit risk cannot moderate capital and liquidity on financial performance of banking. This study also indicates that credit risk strengthens the effect of operational efficiency towards the financial performance of banking.